THE GASTROPROTECTIVE AND ANTIOXIDANT EFFECT OF BELLIS PERENNIS L. (ASTERACEAE) EXTRACTS - Açik, L.; Gurbuz, I.; Demir, H.; Demirci, F.; Göktürk, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Bellis perennis is known as chamomile or papatya” in Anatolia. The plant is used in Turkish folk medicine against tonsillitis, common cold, eczema, eye diseases, and as diuretic, laxative, and diaphoretic [1-3]. In addition, the herb is used for the treatment of peptic ulcer symptoms in various localities [2, 3]. In order to confirm the aclaimed activity on peptic ulcer, aqueous and methanol extracts were prepared from the aerial parts of the plant material and both extracts were tested for their anti-ulcerogenic potential on the ethanol-induced gastric ulcer model using rats. The aqueous and methanol extracts were administered orally at 1100 and 600 mg/kg doses, respectively. Both extracts demonstrated statistically significant anti-ulcerogenic activity (p<0.001). In addition, the aqueous extract of B. perennis showed to possess protective effect with 100% ulcer inhibition. On the other hand, the MeOH extract also demonstrated high gastroprotective effect (95% ulcer inhibition). In vivo pharmacological experiments clearly demonstrated that the relevant extracts of B. perennis showed significant gastroprotection on this model of ulcerogenesis. Additionally, the antioxidant potential of the extracts was evaluated in vitro by DPPH free radical scavenging assay and total antioxidant capacity methods. The results of this study showed that B. perennis extracts is a potential source of natural antioxidants. Chromatographic finger print of these extracts was also documented using LC and LC-MS techniques. Further studies are needed in order to isolate and define the active constituent(s) by bioassay-guided fractionation techniques.Acknowledgements: This study was financially supported by the Turkish Prime Ministry, State Planning Organization (DPT-1998). References: 1. Baytop, T. (1999). Therapy with medicinal plants in Turkey, past and present. Second Ed., Nobel Tp Kitapevi, Istanbul. 2. GÃ¼lay, E.G., Ã–zhatay N., (2006). Turkish J. Pharm. Sci., 3: 73-89. 3. Yazcolu, A., Tuzlac, E. (1995). J. Pharm. Univ. Mar., 11: 333-342